2021
DOI: 10.3390/ijms22084280
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Activation in Neurovascular Damage and Repair Following Ischaemic Stroke

Abstract: Transient or permanent loss of tissue perfusion due to ischaemic stroke can lead to damage to the neurovasculature, and disrupt brain homeostasis, causing long-term motor and cognitive deficits. Despite promising pre-clinical studies, clinically approved neuroprotective therapies are lacking. Most studies have focused on neurons while ignoring the important roles of other cells of the neurovascular unit, such as astrocytes and pericytes. Astrocytes are important for the development and maintenance of the blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 217 publications
2
61
0
Order By: Relevance
“…Stimulation of angiogenesis, as observed by EV treatment, has been shown to improve neurological and motor function in animal stroke models [ 55 ], an effect currently acknowledged as an outcome of EV transfer of proteins, mRNAs, and miRNAs to endothelial cells [ 33 , 56 ] and regulating protein expression [ 57 ]. Additionally, BBB impairment in ischemic stroke, as observed here, has also been documented [ 58 , 59 , 60 ], but its involvement in EVs therapeutic strategies, as indicated in this study, has not been previously reported.…”
Section: Discussionsupporting
confidence: 50%
“…Stimulation of angiogenesis, as observed by EV treatment, has been shown to improve neurological and motor function in animal stroke models [ 55 ], an effect currently acknowledged as an outcome of EV transfer of proteins, mRNAs, and miRNAs to endothelial cells [ 33 , 56 ] and regulating protein expression [ 57 ]. Additionally, BBB impairment in ischemic stroke, as observed here, has also been documented [ 58 , 59 , 60 ], but its involvement in EVs therapeutic strategies, as indicated in this study, has not been previously reported.…”
Section: Discussionsupporting
confidence: 50%
“…For example, in the acute phase of cerebral stroke, microglia quickly react to neuronal damage leading to inflammatory cytokine and chemokine expression. Astrocytes also undergo reactive gliosis and contribute to cytokine expression and inflammation following stroke [ 24 ]. Vascular endothelial cells become activated, with increased expression of selectins and cell adhesion molecules, increased permeability and subsequent attraction, adhesion and infiltration of granulocytes, principally neutrophils, and classical pro-inflammatory monocytes (Ly6C hi in mouse), within hours after injury [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aquaporin-4 (AQP4) water channels, which are highly expressed on the end-feet of astrocytes, play a key role in brain water homeostasis. Following ischemia, the increased expression of proinflammatory mediators and the resulting neurovascular inflammation lead to alterations in AQP4 expression causing cerebral edema [ 53 ]. Kitchen et al revealed that targeting AQP4 not only reduces CNS edema but also leads to accelerated functional recovery following hypoxia [ 54 ].…”
Section: Preclinical Studies Of Exosomes Derived From Nvu Componentsmentioning
confidence: 99%